The impact of internet diffusion on marriage rates: Evidence from the broadband market - Andriana Bellou (Institute for the Study of Labor (IZA), 2013)
The Internet has the potential to reduce search frictions by allowing individuals to identify faster a larger set of available options that conform to their preferences. One market that stands to benefit from this process is that of marriage. This paper empirically examines the implications of Internet diffusion in the United States since the 1990s on one aspect of this market: marriage rates. Exploring sharp temporal and geographic variation in the pattern of consumer broadband adoption, I find that the latter has significantly contributed to increased marriages rates among 21-30 year olds. A number of tests suggest that this relationship is causal and that it varies across demographic groups potentially facing thinner marriage markets. I also provide some suggestive evidence that Internet has likely crowded out other traditional meeting venues, such as through family and friends.
Keywords: J11; J12; D12; R11; O33; 330; internet; broadband; marriage; search